2008
DOI: 10.4269/ajtmh.2008.79.102
|View full text |Cite
|
Sign up to set email alerts
|

Canine Infection by Rickettsiae and Ehrlichiae in Southern Brazil

Abstract: This study evaluated the infection caused by Rickettsia and Ehrlichia agents among dogs in southern Brazil. A total of 389 dogs were tested by the indirect immunofluorescence assay (IFA) for Rickettsia rickettsii, Rickettsia parkeri, Rickettsia amblyommii, Rickettsia rhipicephali, Rickettsia bellii, and Ehrlichia canis. Overall, 42.4% (165/389) of the dogs were seroreactive to at least one Rickettsia species, but only 11 canine sera reacted with another Rickettsia species without reacting with R. parkeri. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 26 publications
5
39
1
15
Order By: Relevance
“…Molecular methods demonstrated similar results for the effects of sex and age relative to infection by E. canis in Cuiaba, State of Mato Grosso (SILVA et al, 2010), and Ilheus and Itabuna, State of Bahia (CARVALHO et al, 2008). This pattern was also observed with serological assessments performed in several Brazilian cities: Cuiaba, State of Mato Grosso (SILVA et al, 2010), Monte Negro, State of Rondonia (AGUIAR et al, 2007), Patos, State of Paraiba (AZEVEDO et al, 2011), and southern cities in the State of Rio Grande do Sul (SAITO et al, 2008). Serological surveys made in the USA (RODGERS et al, 1989), Israel (HARRUS et al, 1997, and Japan (INOKUMA et al, 1999) revealed similar findings.…”
Section: Resultssupporting
confidence: 60%
“…Molecular methods demonstrated similar results for the effects of sex and age relative to infection by E. canis in Cuiaba, State of Mato Grosso (SILVA et al, 2010), and Ilheus and Itabuna, State of Bahia (CARVALHO et al, 2008). This pattern was also observed with serological assessments performed in several Brazilian cities: Cuiaba, State of Mato Grosso (SILVA et al, 2010), Monte Negro, State of Rondonia (AGUIAR et al, 2007), Patos, State of Paraiba (AZEVEDO et al, 2011), and southern cities in the State of Rio Grande do Sul (SAITO et al, 2008). Serological surveys made in the USA (RODGERS et al, 1989), Israel (HARRUS et al, 1997, and Japan (INOKUMA et al, 1999) revealed similar findings.…”
Section: Resultssupporting
confidence: 60%
“…The frequency of E. canis in the serum of dogs in Lavras (MG) was lower than the results observed by Silva et al (19) in Cuiaba (MT), 42.5% (108/254; IFAT ≥40), and by Souza et al (20) in Salvador (BA), 35.6% (168/472; IFAT ≥80). However, Saito et al (21) observed a prevalence of 4.8% (19/389; IFAT ≥80) in Rio Grande do Sul, which was low compared to that obtained in the present study. Importantly, high prevalence rates reported in some studies may be explained by the use of a sample population with clinical suspicion for CME, increasing the possibility of finding dogs with anti-E. canis antibodies.…”
Section: Resultscontrasting
confidence: 55%
“…by IFA, and R. parkeri was the causative agent in 100/389 (25.7%) dogs (SAITO et al, 2008). We hypothesize that low titers may be a result of a less recent or severe infection, probably due to low or non-pathogenic Rickettsia species.…”
Section: Discussionmentioning
confidence: 99%
“…in rural and urban areas in Northern Brazil. Although forest areas are common in the region studied (dog origin) (Figure 2) and may favor tick proliferation (SAITO et al, 2008), no positive animal was found in the rural area. The fact that seropositive dogs were found only in urban areas may be explained by tick distribution associated to higher concentration of host species in these areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation